Discourse research and religion: disciplinary use and interdisciplinary dialogues - Johnston, Jay; Stuckrad, Kocku von (De Gruyter, 2021)
Frontmatter -- Contents -- Introduction -- Discourse Analysis as an Anthropology of the Mundane: An Interview -- Entering Discourses: A New Agenda for Qualitative Research and the Sociology of Knowledge -- Religious Discourse and Its Modules -- Historical Discourse Analysis: The Entanglement of Past and Present -- Whose Voice Is This? The Multicultural Drama from CDA and DST Perspectives -- Some Important Conceptual Lines of Discourse Theories in Cultural Studies of Religion -- The Power Politics of 'Religion': Discursive Analysis of Religion in Political Science and International Relations -- Religion, Discourse, and the Economy Question: Fraught Issues in Market Societies -- Dynamics of the Human Rights Discourse on Freedom of Religion - Observed from the Religious Studies Angle -- Gender and Its Vicissitudes -- 'Beyond' Language? Ecology, Ontology, and Aesthetics -- Index of Key Terms -- Index of Places -- Index of People